Corpo-catedral: entre o teatro evangelizador e a poética de uma paixão subversiva - CHAGAS, Thiago Batista das (2023)
This work discusses my trajectory of theater in churches, which I call here evangelizing, and the possibilities of bodies that subvert. And in this case, my body, in which I present a poetics of a Black Christ in the context of current violence. The theme of the work is CORPO-CATEDRAL: between evangelizing theater and the poetics of a subversive passion that was constructed as follows: a written text in which I transcribe my trajectory in theater in Igrejas and a video performance of a fragment of the Passion of Christ brought to current reality – the meeting of Jesus with Mary, but a contemporary passion in which Christ is represented by a black man shot dead and Mary is represented by a transsexual woman. The work subverts the stereotype of a white, European, blue-eyed Christ. Therefore, we intend to reflect on the issue of racism and the vulnerability of black bodies in our society that have been attacked and killed simply for being black. It is important to highlight how a boy (Thiago) engaged in an evangelical church, a “servant” of Christ, musician and actor manages to subvert and rise up through theatrical art, creating lines of flight from the normativity of a body-cathedral (fixed, “without” possibilities movement) to a subversive body (video performance).